2019
DOI: 10.1002/cncr.32433
|View full text |Cite
|
Sign up to set email alerts
|

The association of pharmacy fill synchronization with breast cancer endocrine therapy adherence

Abstract: Background One‐third to one‐half of patients prescribed adjuvant endocrine therapy are nonadherent during the recommended 5‐year endocrine therapy course. This study investigated whether poor pharmacy synchronization of medication fills (requiring refills on different days) acts as a barrier to adherence. Methods A cohort of older women with stage 0 to III endocrine receptor–positive breast cancer in 2011 was identified from the Surveillance, Epidemiology, and End Result–Medicare claims‐linked cancer registry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…9,11 Prior studies of adherence in Medicaid-insured women reported that 55% to 60% were adherent in the first year, compared with 84% of Medicare-insured women. 15,17,18,21,[37][38][39] These differences suggest a role for insurance status and/or incomes in adherence trends; these findings may also be attributed to age differences between the 2 populations, although this seems less likely given the strong association between socioeconomic status and medication costs and treatment adherence. 37,40 Fewer studies have examined continuation of AET in any population of patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…9,11 Prior studies of adherence in Medicaid-insured women reported that 55% to 60% were adherent in the first year, compared with 84% of Medicare-insured women. 15,17,18,21,[37][38][39] These differences suggest a role for insurance status and/or incomes in adherence trends; these findings may also be attributed to age differences between the 2 populations, although this seems less likely given the strong association between socioeconomic status and medication costs and treatment adherence. 37,40 Fewer studies have examined continuation of AET in any population of patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when prescribing endocrine therapy, oncologists can recommend synchronization programs to their patients and prescribe quantities that allow alignment of refills, which can minimize trips to the pharmacy. Neuner et al's study also found that patients with 90‐day prescriptions were also slightly more likely to be adherent (odds ratio, 1.008) in comparison with patients receiving 30‐day prescriptions, and this provides another tool that physicians can use to improve adherence while reducing patient copays.…”
mentioning
confidence: 90%
“…In this issue of Cancer , Neuner et al explore the relationship of breast cancer patients' prescription refill synchronization and patient adherence to adjuvant endocrine therapy. Prescription refill synchronization refers to the alignment of prescription refills to the same pharmacy visit and is hypothesized to improve medication adherence by reducing the total number of trips that a patient must take to the pharmacy and thus the financial and logistical barriers to medication adherence.…”
mentioning
confidence: 99%
See 2 more Smart Citations